HRD MECHANISMS IN HEALTH CARE SECTOR IN J&K: A COMPARATIVE STUDY - S.A. Mufeed; Qurrat.A. Hamdani (European Scientific Journal, ESJ, 2013)
Human Resource Development (HRD) is a framework for the expansion of human capital within an organization. It is a combination of training and education that ensures the continual improvement and growth of both the individual and the organization.HRD mechanisms fall in one of the elements of HRD climate, which measure the extent, to which the HRD mechanisms are implemented. Various HRD mechanisms such as training & development, career planning, career development, career counselling, performance appraisal system, organization development, quality of work life, workers participation in management are being used in various organizations for building HRD climate. Research on HRD mechanisms at National and International level, particularly in Health care sector is limited. Taking into consideration the limited study on Health care sector, the present study was undertaken on two hospitals-SKIMS & SMHS in the state of J&K with special focus on Performance Appraisal system (PAS) and Training and Development (T&D).